PATROL SHIP SELECTION ANALYSIS TO SUPPORT MARITIME SECURITY OPERATIONS IN THE WORKING AREA OF LANTAMAL V SURABAYA - Rifki Najib; Ahmadi Ahmadi; Joko Purnomo (Indonesian Naval Technology College STTAL, 2021)
In order to maintain maritime security, especially in the Lantamal V Surabaya working area, the patrol ship unit elements must be ready to deal with all incidents with quick responses. Therefore, it is very necessary to have the most precise patrol ship specifications to carry out tasks that are faced with frequent vulnerabilities, and are also faced with a limited state defense budget. This research proposes the use of the integration of the Fuzzy MCDM and BCA methods in selecting the type of Satrol ship. The Fuzzy MCDM method is considered very appropriate for the problem of fuzzy criteria weights. The BCA method is used to analyze the benefits and costs that will occur as a consequence of the operation of the ship. Based on this research, it is concluded that from the available alternatives, the best Patrol ship that should have been selected for the development/ procurement of Satrol ship is